Droplet size distribution, atomization mechanism and dynamics of dental aerosols. (November 2022) - Kayahan, Emine; Wu, Min; Van Gerven, Tom; Braeken, Leen; Stijven, Lambert; Politis, Constantinus; Leblebici, M. Enis
Abstract: Since the outbreak of COVID-19 pandemic, maintaining safety in dental operations has challenged health care providers and policy makers. Studies on dental aerosols often focus on bacterial viability or particle size measurements inside dental offices during and after dental procedures, which limits their conclusions to specific cases. Fundamental understanding on atomization mechanism and dynamics of dental aerosols are needed while assessing the risks. Most dental instruments feature a build-in atomizer. Dental aerosols that are produced by ultrasonic or rotary atomization are considered to pose the highest risks. In this work, we aimed to characterize dental aerosols produced by both methods, namely by Mectron PIEZOSURGERY® and KaVo EXPERTtorque™. Droplet size distributions and velocities were measured with a high-speed camera and a rail system. By fitting the data to probability density distributions and using empirical equations to predict droplet sizes, we were able to postulate the main factors that determine droplet sizes. Both dental instruments had wide size distributions including small droplets. Droplet size distribution changed based on operational parameters such as liquid flow rate or air pressure. With a larger fraction of small droplets, rotary atomization poses a higher risk. With the measured velocities reaching up to 5 m s −1, droplets can easily reach the dentist in a few seconds. Small droplets can evaporate completely before reaching the ground and can be suspended in the air for a long time. We suggest that relative humidity in dental offices are adjusted to 50% to prevent fast evaporation while maintaining comfort in the office. This can reduce the risk of disease transmission among patients. We recommend that dentists wear a face shield and N95/FFP2/KN95 masks instead of surgical masks. We believe that this work gives health-care professionals, policy makers and engineers who design dental instruments insights into a safer dental practice. Highlights: Two dental instruments, Mectron PIEZOSURGERY® and KaVo EXPERTtorque™, are studied. Considering droplet sizes and evaporation rate, FFP2/KN95/N95 masks are recommended. The design of the dental equipment can be improved to produce larger droplets. At the reported velocities (∼2 m s −1 ), droplets can reach the dentist instantly. Adjusting the relative humidity to 50% was suggested to keep the droplets larger.